Інокультурні реалії та етнообрази в "Щоденниках" Олеся Гончара - Приліпко, І.Л. (Слово і Час, 2019)
У статті з'ясовано специфіку зображення у “Щоденниках” О. Гончара інших країн та народів.
Розкрито особливості авторського сприйняття інокультурних реалій, визначено чинники
формування етнообразів та своєрідність їх репрезентації на сторінках “Щоденників”. У контексті
співвідношення Свого і Чужого просторів простежено позицію письменника щодо інших народів
та культур, формування нестереотипних уявлень про Іншого/Чужого. The paper deals with the specific features of describing foreign countries and nations in O. Honchar’s
“Diaries”. The presented research shows particular details of foreign realities in the author’s perception,
classifies the factors of forming ethnic images, and evaluates the originality of their representation
in “Diaries”. In the context of the Own and Alien space correlation O. Honchar’s position becomes
visible. He underlines the absence of stereotypes and domination of shared spiritual people’s values
in forming the conception of a stranger. Foreign cultural realities and ethnic images, represented in
“Diaries”, were the results of the author’s detailed observation and deep penetration into the facts of
spiritual and material culture, mental peculiarities, history and present situation of different nations
(Georgians, Jews, Russians, Portuguese, Indians, Americans, Japanese and others). The concept
Other/Alien is formed involving such points as projection on the Own space, comparison of different
foreign cultural facts with the realities of Ukrainian context. The diary notes represent the evolution of
the author’s reception. The war period notes demonstrate domination of the Alien in the process of
perceiving foreign culture, which is caused by the tragic war situation and longing for the native land.
The post-war period notes show O. Honchar’s reflections on his war experience, the writer’s interest
in cultural, historical, and social peculiarities of certain people. The reproduction of foreign cultural
realities evolved. Ethnic images were designed on the basis of observation, impressions, generalization,
and comparison of topographic, ideological, artistic, and historical peculiarities. They all formed an
ethnomental image of a separate nation. The ethnic images, represented in O. Honchar’s “Diaries”,
are based on humanistic values. They emphasize the idea of spiritual universality of different people,
underlining the facts that unite representatives of different countries.